Genome-wide identification of long intergenic non-coding RNAs of responsive to powdery mildew stress in wheat (Triticum aestivum) - Cao, Peina; Wang, Youning; Ma, Zhaolan; Xu, Xiao; Ma, Dongfang; Yang, Lijun (Frontiers in Plant Science, 2023)
Wheat powdery mildew caused by Blumeria graminis f. sp. tritici, is one of the most serious foliar diseases of wheat, causing grain yield and quality degradation by affecting plant photosynthesis. It is an effective method to improve the disease resistance of wheat plants by molecular breeding. With the continuous development of sequencing technology, long intergenic noncoding RNAs (lincRNAs) have been discovered in many eukaryotes and act as key regulators of many cellular processes. In this study, 12 sets of RNA-seq data from wheat leaves pre-and post-pathogen infection were analyzed and 2266 candidate lincRNAs were identified. Consistent with previous findings, lincRNA has shorter length and fewer exons than mRNA. The results of differential expression analysis showed that 486 DE-lincRNA were selected as lincRNAs that could respond to powdery mildew stress. Since lincRNAs may be functionally related to their adjacent target genes, the target genes of these lincRNAs were predicted, and the GO and KEGG functional annotations of the predicted target genes were performed. Integration the functions of target genes and the biological processes in which they were involved uncovered 23 lincRNAs may promote or inhibit the occurrence of wheat powdery mildew. Co-expression patterns of lincRNAs with their adjacent mRNA showed that some lincRNAs showed significant correlation with the expression patterns of their potential target genes, and suggested an involvement of lincRNAs in pathogen stress response.